Resistance mechanisms of immune checkpoint inhibition in lymphoma: Focusing on the tumor microenvironment - Zhang, Chunlan; Wang, Leiming; Xu, Caigang; Xu, Heng; Wu, Yu (Frontiers in Pharmacology, 2023)
Immune checkpoint inhibitors (ICIs) have revolutionized the therapeutic strategies of multiple types of malignancies including lymphoma. However, efficiency of ICIs varies dramatically among different lymphoma subtypes, and durable response can only be achieved in a minority of patients, thus requiring unveiling the underlying mechanisms of ICI resistance to optimize the individualized regimens and improve the treatment outcomes. Recently, accumulating evidence has identified potential prognostic factors for ICI therapy, including tumor mutation burden and tumor microenvironment (TME). Given the distinction between solid tumors and hematological malignancies in terms of TME, we here review the clinical updates of ICIs for lymphoma, and focus on the underlying mechanisms for resistance induced by TME, which play important roles in lymphoma and remarkably influence its sensitivity to ICIs. Particularly, we highlight the value of multiple cell populations (e.g., tumor infiltrating lymphocytes, M2 tumor-associated macrophages, and myeloid-derived suppressor cells) and metabolites (e.g., indoleamine 2, 3-dioxygenase and adenosine) in the TME as prognostic biomarkers for ICI response, and also underline additional potential targets in immunotherapy, such as EZH2, LAG-3, TIM-3, adenosine, and PI3Kδ/γ.